Why the Ex-Communist Countries Should Take the 'Middle Way' to the Market - Kenneth Koford (Levy Economics Institute of Bard College, 1991)
The ex-communist countries of Europe as well as Soviet Union want to find a way out of the command economy to a market system. The common advice (e.g., Lipton and Sachs, Kornai) has been to go quickly "all the way" to a fully capitalist economy. The difficulties of this policy are now becoming clear. This paper argues that a "middle way" with many socialist elements is an attractive path for these countries, for both the transition and as a long-term goal. Economic reform of ex-communist countries must be based on two core elements. First, the primacy of law and stable private property rights must be assured. Second, free markets must be the basis of economic relations. How could reform then be a middle way? First, firms must be independent entities owned by shareholders and responsible for making a profit, but the owners can include local, provincial (republic) and national governments, workers, and social institutions providing pensions and insurance. Government ownership has not made Volkswagen, Lufthansa or Japan Air Lines economic failures. Second, market are institutions that must be developed. It is particularly important for a society without accepted norms and laws regarding market behavior to develop them, and to evolve efficient private contracts. Government legal codes can help. Finally, regulation can provide some of the security of socialist systems and Western welfare states. The economic case for a middle way is supported by its widespread success, including Austria, Germany's "social market" economy, Sweden, Canada and Japan. The cultural case is based on an economy's need to be reasonably consistent with its society's customs and norms. It is less of a shock for an ex-communist society to move to the "middle way" than to a purely capitalist society.
Keywords: 330